PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POP-UP BOOK TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V MI MUHAMMADIYAH PEKALONGAN - Issa Virnama Della; Dayu Rika Perdana; Siti Nuraini; Mujiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem of this study is the lack of critical thinking skills of students in the Pancasila Education subject of grade V MI Muhammadiyah Pekalongan which is still in the sufficient category. This study aims to determine the effect of the use of the Problem Based Learning (PBL) model assisted by pop-up book media on students' critical thinking skills. This study uses a quantitative approach with a quasi-experimental design. The study population is all grade V students, with two classes as samples, namely the control class using Discovery Learning assisted by PPT and the experimental class using Problem Based Learning (PBL) assisted by pop-up book media. The results of the study indicate that there is an effect of the use of the Problem Based Learning (PBL) model assisted by pop-up book media on students' critical thinking skills.